2020
DOI: 10.1002/slct.201902998
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Host Guest Inclusion Complexation of Cyclic Oligosaccharide with Industrially Potent Dye in Different Phases by Physicochemical Contrivance

Abstract: The inclusion phenomena of β-Cyclodextrin and Alizarin complexone was investigated by 1H NMR, 2D ROESY, UV-Visible Spectroscopy, Fluorescence Spectroscopy, HRMS and SEM study. The change in chemical shift values in 1H NMR study established the possibility of interactions between the corresponding protons of β-Cyclodextrin and AC molecule, which was further confirmed by the appearance of cross peaks in 2D ROESY spectrum. The Job plot method gave the host-guest stoitiometric ratio to be 1 : 1. The association co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…54 It can be seen that the H-3 and H-5 protons in the inclusion complex of a-CDPL with 4aminoazobenzene have been shifted from 3.89 ppm and 3.73 ppm to 3.90 ppm and 3.74 ppm, respectively, which indicates the entrance of the 4-aminoazobenzene. 55 What is more, the chemical shifts of 4-aminoazobenzene in DMSO-d 6 was compared with that of the inclusion complex of a-CDPL with 4-aminoazobenzene. 56 It was found that the chemical shifts of 3, 5, 10-H in 4-aminoazobenzene have been changed, which suggested that the phenyl part of 4-aminoazobenzene was included in the cavity of a-CDPL.…”
Section: Mechanism Of Chiral Inductionmentioning
confidence: 99%
“…54 It can be seen that the H-3 and H-5 protons in the inclusion complex of a-CDPL with 4aminoazobenzene have been shifted from 3.89 ppm and 3.73 ppm to 3.90 ppm and 3.74 ppm, respectively, which indicates the entrance of the 4-aminoazobenzene. 55 What is more, the chemical shifts of 4-aminoazobenzene in DMSO-d 6 was compared with that of the inclusion complex of a-CDPL with 4-aminoazobenzene. 56 It was found that the chemical shifts of 3, 5, 10-H in 4-aminoazobenzene have been changed, which suggested that the phenyl part of 4-aminoazobenzene was included in the cavity of a-CDPL.…”
Section: Mechanism Of Chiral Inductionmentioning
confidence: 99%